Oxytocin administration selectively improves olfactory detection thresholds for lyral in patients with schizophrenia. (March 2015) - Woolley, J.D.; Lam, O.; Chuang, B.; Ford, J.M.; Mathalon, D.H.; Vinogradov, S.
Highlights: Our data showed that intranasal oxytocin selectively increased the odor detection threshold for lyral, which is a low cAMP activator. This suggests that oxytocin may increase odor detection threshold via an increase in cAMP. Instranasal oxytocin had no effect on odor detection threshold levels in healthy controls. Olfactory deficits in patients with schiozphrenia may be allievated with administration of intranasal oxytocin. Summary: Background: Olfaction plays an important role in mammalian social behavior. Olfactory deficits are common in schizophrenia and correlate with negative symptoms and low social drive. Despite their prominence and possible clinical relevance, little is understood about the pathological mechanisms underlying olfactory deficits in schizophrenia and there are currently no effective treatments for these deficits. The prosocial neuropeptide oxytocin may affect the olfactory system when administered intranasally to humans and there is growing interest in its therapeutic potential in schizophrenia. Methods: To examine this model, we administered 40 IU of oxytocin and placebo intranasally to 31 patients with a schizophrenia spectrum illness and 34 age-matched healthy control participants in a randomized, double-blind, placebo-controlled, cross-over study. On each test day, participants completed an olfactory detection threshold test for two different odors: (1) lyral, a synthetic fragrance compound for which patients with schizophrenia have specific olfactory detection threshold deficits, possibly related to decreased cyclic adenosine 3′, 5′-monophosphate (cAMP) signaling; and (2) anise, a compound for which olfactory detection thresholds change with menstrual cycle phase in women. Results: On the placebo test day, patients with schizophrenia did not significantly differ from healthy controls in detection of either odor. We found that oxytocin administration significantly and selectively improved olfactory detection thresholds for lyral but not for anise in patients with schizophrenia. In contrast, oxytocin had no effect on detection of either odor in healthy controls. Discussion: Our data indicate that oxytocin administration may ameliorate olfactory deficits in schizophrenia and suggest the effects of intranasal oxytocin may extend to influencing the olfactory system. Given that oxytocin has been found to increase cAMP signaling in vitro a possible mechanism for these effects is discussed.